Subjective symptoms and their evolution in a small group of magnetic resonance imaging (MRI) operators recently engaged. (3rd July 2015) - Zanotti, G.; Ligabue, G.; Gobba, F.
Abstract: Using a specific questionnaire, we examined subjective symptoms in a group of 17 physicians (9 males and 8 females, mean age 32.9 ± 3.71), attending a Postgraduate Medical School in Radiology and engaged in MRI for less than 1 year. Sixteen subjects (94%) reported the presence of at least one of the investigated symptoms during the period of MRI activity. The main symptoms were: unusual drowsiness/tiredness (88%), concentration problems (82%), headaches (76%), sleep disorders (47%), nausea (47%), illusion of movement (47%) and dizziness/vertigo (35%); the former two were subjectively related to MRI by the majority of the operators. These symptoms appeared (or worsened) in more than 15 min and, in the vast majority disappeared 30 min, or more, after the end of exposure. In 13 subjects (81%), the symptom (or some symptoms) appeared at least weekly. In this small group of health care workers recently exposed to MRI, the prevalence of subjective symptoms was higher than reported in other similar studies but, notably, the majority of subjects (77%) reported a regression within 4–8 weeks, suggesting some form of adaptation.